Let's go teaching and learning digital of fundamentals of Islamic banking application / Zanirah Mustafa@Busu ... [et al.] - Mustafa@Busu, Zanirah; Nik Din, Nik Muniyati; Awang@Ab Rahma, Nurul Hidayah n; Noor Zainan, Nurul Izzah; Mohd Firdaus Kozako, Intan Nurul'ain; Mat Jusoh, Nor Asmira; Ismail, Mohd Khairul Anuar; Junoh, Noraini; Yusuf, Norazmila; Musa, Muhammad Fadhli (2022)
CTU 351 is a compulsory course for every Islamic banking student. This is because this course introduces the basics to the Islamic banking system through shariah principles. The application of products according to the shariah concept used in the Islamic banking system should be understood by every student. However, there are still constraints for students in understanding the Islamic banking system and also the shariah principles used in this course. Therefore, the development of teaching and learning applications has been developed for the basic course of Islamic banking system CTU351 to help students and instructors to facilitate understanding in the course. Let's go Teaching and Learning Digital of Fundamentals of Islamic Banking Application is a platform created for students who enrol in the Fundamental of Islamic Banking (CTU351) course. This application helps students to retrieve materials such as course information, modules, slides, past year questions, calculation exercises, and lecture videos. This application are develop for provide a platform where students can easily access information and materials for CTU351 course. Digital Teaching and Learning: The fundamentals of Islamic banking (CTU 351) is a dynamic, visible, responsive and effective application representing the one-stop centre of information in serving students and the community. Thus, innovative product design educationally represents a digital combination of workable technology and current learning and teaching needs that properly qualify with appropriate items to accurately perceive the fundamentals of Islamic Banking. This application can use to all education in Islamic Banking and any Islamic financial system. This application will accordingly am effectively in understanding practically in Islamic Banking System.